Competence and evaluation: the design of educational action - Scalcione, Vincenzo Nunzio (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
In the globalized society, the pedagogical system is affected by interventions that, even following the pandemic event, have changed the perspective of action; in the didactic planning emerges the need to activate flexible styles, able to implement the concept of lifelong learning, which has become a tool for understanding the dynamics of the current knowledge society. Thus, cognitive places open to the construction of knowledge, reconfigurable, able to respond to new functional needs, find realization. Within such scenarios, the concept of competence assumes particular importance, understood as the multifaceted ability to adapt to intervening and future changes, hybridization of theory with practice The elements that determine the writing of similar educational orientation maps are analyzed, within the frame of the methods of designing and evaluating performance, in educational action.